Quality of referral, admission status, and outcome of neonates referred to pediatric emergency of a tertiary care institution in North India - Neeraj Mishra; Shiv Sajan Saini; Muralidharan Jayashree; Praveen Kumar (Indian Journal of Community Medicine, 2022)
Background: This study was planned to study the existing status of neonatal transport in North India after the introduction of National Ambulance Service (NAS). We evaluated the quality of referral, admission status, and outcome of referred neonates. Materials and Methods: We enrolled neonates admitted between March 2016 and October 2016, excluding neonates referred from the outpatient department. Information was collected from referral slips, interviewing accompanying persons and observation. Results: Sixty-one percent were referred from government hospitals with “sick newborn care units” contributing to maximum. The main mode of transport was ambulance in 80% and referral notes were available in the majority but incomplete in majority. Sepsis (39%), jaundice (16%), and birth asphyxia (13%) were the most common diagnoses. Half of the neonates were hemodynamically unstable. Twenty-seven percent had poor circulation, 15% were hypoxic, 9% hypoglycemic, and 8% hypothermic. Twenty-two percent either died or “left against medical advice” with a high probability of death. Conclusion: NAS is utilized for transporting neonates. However, there are quality gaps which need attention to develop it into efficient referral system.